Cu-Mg-O thin films by RF magnetron co-sputtering: Their band offsets with CdS in heterojunction solar cells - Sanal, K. C.; Pushpan, Soorya; Nair, P. K.; Nair, M. T. S. (Quimica Hoy, 2022)
We report on Cu-Mg.O thin films of 100 - 300 nm in thickness produced by radio frequency (RF) reactive sputtering from Cu and Mg-metal targets in an argon-oxygen ambient. The amount of Mg in the thin films was varied through changing the RF power applied at the Mg target. When the Mg content in the Cu-Mg-O film changed from 0 to 0.3, the optical bandgap increased from 1.73 eV to 2.13 eV, and the electrical conductivity decreased from 9 x 10-3 Ω-1 cm-1(CuxO) to 6.7x 10-5 Ω-1 cm-1(Cuo7/Mg0.30). Solar cells of these films, FTO/ CdS/Cu0.85Mg0.15O/C-Ag, showed a short circuit current density of 2.86 mA/cm2 an open circuit voltage of 378 mV, and power conversion efficiency of 0.25%. X-ray photo-electron spectroscopy depth profile analyses of the interfaces suggest a negative conduction band offset in CdS/Cu0.85Mg0.15O( — 0.74 eV) as well as in CdS/CuxO (0.9 eV) solar cells.